Sikap dan keinginan tingkah laku pengguna dalam pemilihan telefon bimbit: kajian kes di Bandar Baru Bangi, Selangor - Zalina Mohd Ali,; Mohd Aftar Abu Bakar,; Zamira Hasanah Zamzuri,; Nora Muda,; Nur Jumaadzan Zaleha Mamat,; Petir Papilo,; Nur Riza M Suradi, (Penerbit ukm, 2009)

(untitled)
Information on consumer behavioural intention in choosing a product is important for an organisation to determine product promotion and marketing strategies. In this study, we use Fishbein Model to analyse the consumer behavioural intention regarding the choice of the mobile phone brand. Three popular mobile phones were chosen. The study involved a questionnaire-based survey on 112 respondents of mobile phone users. The results show that there exist tendencies in the majority of the customers to choose a particular brand from others